Greasing wheels of cell-free therapies for cardiovascular diseases: Integrated devices of exosomes/exosome-like nanovectors with bioinspired materials - Xuerui Chen; Liyun Zhu; Jianyun Liu; Yi Lu; Longlu Pan; Junjie Xiao (Extracellular Vesicle)
Mortality and morbidity of cardiovascular diseases (CVDs) including ischemic heart disease (IHD) and heart failure (HF) are arising worldwide. Once cardiomyocyte is impaired, it is challenging to regenerate which is largely limited by the irreversibility of cell cycle after birth. Emergent approaches in regenerative medicine head toward the application of extracellular vesicles (EVs) such as exosomes in next-generation cell-free treatment strategies for CVDs, attributed to their repair promotion. However, naked exosomes undergo major obstacles of high clearance by the mononuclear phagocyte system and transient retention of exosomes in transplanted areas, eventually failing in the endogenous repair. Strategies optimizing matrix materials to release exosomes in a targeted, sustained and minimally invasive manner will pave the way for empowering cardiac repair and regeneration. In this review, we extensively summarize the integrated devices of exosome or exosome-like nanovectors with biomaterials for treating CVDs. Furthermore, we provide recommendations on how combinations of exosomes/ biomaterials (e.g. hydrogels, stents, cell sheets, cardiac patches, microneedles, spray and 3D tissue matrix) increase the success rate of cell-free therapies which will boost cardiac repair and regeneration in the clinical settings of CVDs.